Modeling and Inference of Insurance Sector Development on Nigeria Economic Growth - Idi, Danjuma; Stephen, Mathew (Darul Yasin Al Sys, 2024)
This empirical study investigated the impact of insurance sector development on economic growth in Nigeria, covering the period 1999-2022. Utilizing statistical techniques, including Augmented Dickey-Fuller (ADF) tests, regression modeling, Lagrange multiplier (LM) tests, and the Breusch-Pagan-Godfrey test for heteroskedasticity, the study revealed critical insights into the dynamic relationship between insurance sector and economic performance. The ADF test results indicated that the data series were stationary after differencing, confirming an integrated order of one (I(1)). The regression analysis revealed a statistically significant positive impact of total insurance investment (TII) on economic growth in Nigeria, with a coefficient estimate of 0.753 (p < 0.01). Conversely, no significant relationship was found between total claims paid by insurance companies and economic growth in Nigeria, with a coefficient estimate of 0.033 (p > 0.05).Diagnostic tests revealed no evidence of serial correlation in residuals at lag 1, indicating no systematic pattern, and no significant heteroskedasticity was detected, signifying no systematic variance in residuals with changes in independent variables. Based on these findings, the study recommends that policymakers prioritize implementing measures to enhance the regulatory environment and promote innovation within the insurance industry, among other policy implications.